2018
DOI: 10.1002/jnr.24372
|View full text |Cite
|
Sign up to set email alerts
|

Perihematomal edema: Implications for intracerebral hemorrhage research and therapeutic advances

Abstract: In humans, perihematomal edema (PHE) is considered to be a radiological marker of secondary injury following intracerebral hemorrhage (ICH). There is also evidence that PHE might contribute to poor outcome in ICH patients. Given the rising interest in secondary injury after ICH as a therapeutic target, PHE is becoming increasingly used as a proof‐of‐concept surrogate measure to assess the potential efficacy of various therapeutic interventions in clinical trials. We review the pathophysiology of PHE and its ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 28 publications
(48 reference statements)
0
60
0
Order By: Relevance
“…Based on this, we designed a flexible conformal MIPS sensor that is better suited for targeting local change of dielectric properties which reflects the CE progression. More importantly, Selim & Norton (2020) have suggested that investigation and interventions targeting CE should be conducted in the early stage (within hours of ICH onset) and maintained for several days. A user-friendly solution between monitoring modality and patients is critical for long-term practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, we designed a flexible conformal MIPS sensor that is better suited for targeting local change of dielectric properties which reflects the CE progression. More importantly, Selim & Norton (2020) have suggested that investigation and interventions targeting CE should be conducted in the early stage (within hours of ICH onset) and maintained for several days. A user-friendly solution between monitoring modality and patients is critical for long-term practice.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in 596 patients found that the increasing PHE expansion rate in the first 72 h after ICH is associated with higher mortality (Murthy et al, 2015). The change rate of CE growth is a new, emerging parameter and might represent a better indicator for poor outcome, compared with the commonly image-based diagnosis (Selim & Norton, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…22 Hematoma volume is thought to be a particular risk factor for delayed PHE as brain parenchyma is exposed to a higher burden of erythrocyte degradation products over time. 28 Due to its impact on secondary injury, PHE is a target for therapeutic intervention in ICH. Studies on PHE evolution suggest interventions targeting PHE should be initiated early and maintained over the first 3 to 7 days as possible.…”
Section: Pathophysiology Of Secondary Neurological Injurymentioning
confidence: 99%
“…Studies on PHE evolution suggest interventions targeting PHE should be initiated early and maintained over the first 3 to 7 days as possible. 26,28 Disordered cerebral autoregulation and secondary ischemia in ICH: Disordered cerebral autoregulation (CA) and secondary ischemia in ICH too is an important cause for further secondary injury. 29 Remote ischemic lesions are found in approximately 25% of patients 30 days after ICH.…”
Section: Pathophysiology Of Secondary Neurological Injurymentioning
confidence: 99%
“…HBO may become a practical clinical approach to accelerate unconsciousness recovery in patients. The final two papers focus on clinical prognosis and assessment of the quality of care. In clinic, perihematomal edema (PHE) is a radiological marker of secondary injury following ICH and becoming increasingly used as a proof‐of‐concept surrogate measure to assess the potential efficacy of various therapeutic interventions in clinical trials (Selim & Norton, ). Dr. Selim reviewed the pathophysiology of PHE, its prognostic significance for clinical outcomes, and irregularity in PHE measurement methods in order to determine the advantages of exploiting PHE as a marker to evaluate the efficacy of interventions aiming to decrease secondary injury in ICH (Selim & Norton, ).…”
Section: New Molecular Pathways and Treatments For Secondary Injuriesmentioning
confidence: 99%